2008
DOI: 10.1039/b718954k
|View full text |Cite
|
Sign up to set email alerts
|

Atomic spectrometry update. Environmental analysis

Abstract: This is the twenty-forth annual review published in JAAS of the application of atomic spectrometry to the chemical analysis of environmental samples. This Update refers to papers published approximately between September 2007 and August 2008. In the analysis of air, work is focused on the need to collect and characterise ultrafines, i.e. particles below 100 nm in size, and such research is being facilitated through the development of air sampler technologies for subsequent off-line analysis of particles and ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 323 publications
(314 reference statements)
0
28
0
Order By: Relevance
“…23 Procedures may be divided into those based on selective, sequential extraction that are designed to estimate how much arsenic may be available for uptake by plants and those designed to extract all species so that they can be separated and quantified. While these latter procedures are, in principle, more useful there are considerable difficulties with ensuring that (a) all of the relevant species are extracted, and (b) there is no interconversion.…”
Section: -22mentioning
confidence: 99%
“…23 Procedures may be divided into those based on selective, sequential extraction that are designed to estimate how much arsenic may be available for uptake by plants and those designed to extract all species so that they can be separated and quantified. While these latter procedures are, in principle, more useful there are considerable difficulties with ensuring that (a) all of the relevant species are extracted, and (b) there is no interconversion.…”
Section: -22mentioning
confidence: 99%
“…Fluorescence emission spectroscopy was used to monitor the competition event. The fluorescence quenching observed for Zn 2+ (1)(2)(3)(4). Besides, Zn 2+ ions to all the four compounds in ethanol, and huge fluorescence quenching are ascribed at 450-460 nm (Fig.…”
Section: +mentioning
confidence: 88%
“…The pledge of fluorescent detection is superior to other analytical measurements is very high promise, sensitivity, simplicity of use, and low expenditure (Butler et al 2008;Yanagida et al 2009; Szmacinski et al 1993;Lakowicz et al 1983;Czarnik et al 1994; Lakowicz et al 1995). Zinc ion (Zn 2+ ) is the key note of awareness ascribing to the biological significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most comprehensive database of literature and research on elemental speciation could be found at www.speciation.net, the official Web site of the European Virtual Institute for Speciation Analysis (EVISA; 2008). These advances have been also collected and described in various review articles during the last decade (Ali et al, 2005;Butler et al, 2005Butler et al, , 2006Butler et al, , 2007Butler et al, , 2008Cave et al, 2001;Li et al, 2008;Moldovan et al, 2004;Wang, 2007;Wuilloud & Altamirano, 2006;Yip & Sham, 2007). It is not our intention to perform an extensive literature review on analytical methods for elemental speciation, in general.…”
Section: Analytical Methods For the Determination Of Metal And Metallmentioning
confidence: 96%